USING THINK-PAIR-SHARE TO IMPROVE SPEAKING ACHIEVEMENT OF THE SECOND SEMESTER ENGLISH STUDY PROGRAM OF TRIDINANTI UNIVERSITY PALEMBANG - Manurung, Jenny Elvinna (English Community Journal, 2017)
The study aimed at improving the speaking achievement of the second semester students of Tridinanti Palembang by using Think-Pair-Share strategy (TPR). This study was an action research study. The steps in conducting the study were planning, actions and observation of action and reflections. The population of the study was all of the second semester students of Tridinanti University in the academic year 2016/2017. The sample used one class (10students). The data collections used by the researcher were tests and observation. The learning improvement indicators included in two things; (1) learning achievement, (2) teaching and learning process. In the study, the implementation was conducted into two cycles. The results showed that the average score of studentsÃ¢â¬â¢ speaking achievement was 66 in cycle I and the observation result was 62.82. The result had not been reached the target yet that was >70. At least more than 85% students could achieve the score above 70. Thus, cycle II was necessary to be implemented. In cycle II, the average score of speaking test was 81and the observation result was 81.06. The students had reached the target and the cycle was stopped. In conclusion, the implementation of TPR had brought significant improvement to the studentsÃ¢â¬â¢ speaking achievement.